PENERAPAN MEDIA CONGKLAK DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PADA OPERASI PERKALIAN DASAR - Sri Andini Yamporo; Asriyati Nadjamudin; Mifta Huljannah (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to describe the application of Congklak media in mathematics learning, especially on the material of basic multiplication operations for third-grade students at SDN 9 Limboto and improve the arithmetic ability of third-grade students at SDN 9 Limboto on basic multiplication operations after the application of Congklak learning media. This type of research is classroom action research. The subjects of this study were 27 third-grade students at SDN 9 Limboto. The data analysis techniques used in this study were qualitative and quantitative analysis. Based on the results of the two cycles of research, researchers can conclude that the application of traditional congklak learning media has been proven to significantly improve learning outcomes in basic multiplication operations in third-grade students. This increase can be seen from the increase in classical completeness and the average value of students gradually in each cycle in cycle 1 with a percentage of 61% and cycle II with a percentage of 80%.